Values and Ecosystem Services Provided by Gainesville's Urban Forest in 2016 - Michael G Andreu; Caroline A Hament; David A. Fox; Robert J. Northrop (EDIS, 2019)
The urban forest is a crucial factor in the well-being of a community because of the aesthetics, health benefits, and cost-savings that it provides. The urban forest is our habitat, and we must manage it in ways that will provide the benefits we need and desire. This 3-page fact sheet written by Michael G. Andreu, Caroline A. Hament, David A. Fox, and Robert J. Northrop and published by the UF/IFAS School of Forest Resources and Conservation describes an urban forest ecological analysis conducted in 2016 in Gainesville, Florida, by the University of Florida in partnership with the Parks, Recreation, and Cultural Affairs Department to quantify the vegetation structure, functions, and values of the urban forest. http://edis.ifas.ufl.edu/fr414